2004
DOI: 10.1111/j.0303-6987.2004.00204.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary cutaneous CD30+ anaplastic large cell lymphoma with keratoacanthoma‐like pseudocarcinomatous hyperplasia and marked eosinophilia and neutrophilia

Abstract: Our case illustrates that primary cutaneous ALCL may be associated with KA-like PCH and concurrent marked tissue eosinophilia and neutrophilia. Diagnosis in such cases is challenging both clinically and histologically because the large atypical lymphoid cells may easily be obscured by the massive infiltrates of eosinophils and neutrophils or confused with invasive squamous cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 15 publications
3
44
0
Order By: Relevance
“…In contrast to their findings, the trunk was most frequently involved in our cases, followed by the extremities and head. Furthermore, neutrophil/eosinophil‐rich CALCL is not only confined to ulcerated and purulent lesions – cutaneous manifestations of multiple erythematous painful nodules and keratoacanthoma‐like lesions have also been described 8,9 . As indicated in our series, a variety of clinical manifestations including red nodules, brownish indurated plaques and exophytic masses with or without ulceration or crusting can be found in this variant.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In contrast to their findings, the trunk was most frequently involved in our cases, followed by the extremities and head. Furthermore, neutrophil/eosinophil‐rich CALCL is not only confined to ulcerated and purulent lesions – cutaneous manifestations of multiple erythematous painful nodules and keratoacanthoma‐like lesions have also been described 8,9 . As indicated in our series, a variety of clinical manifestations including red nodules, brownish indurated plaques and exophytic masses with or without ulceration or crusting can be found in this variant.…”
Section: Discussionsupporting
confidence: 71%
“…Because the tumour cell compartment can be obscured by its intense inflammatory background, the diagnosis of neutrophil‐rich ALCL is challenging, especially in skin, which is a predilection site for non‐neoplastic lymphoproliferative diseases. CALCL with extensive neutrophils or eosinophils is extremely rare, with <10 cases reported according to Mann’s criterion 3–9 . Here, we present clinicopathological, immunophenotypic and molecular studies of nine cases with neutrophil/eosinophil‐rich CALCL to delineate further this rare variant and emphasize its differential diagnosis.…”
Section: Introductionmentioning
confidence: 90%
“…PEH in 3 cases presented with a keratoacanthoma-like architecture. 8,9,11 Our ALCL patients who had PEH on histology presented with 1 or 2 nodules. We had follow-up on 3 of them.…”
Section: Discussionmentioning
confidence: 89%
“…5 PEH occasionally occurs in association with lymphomas, most commonly nasal natural killer/T-cell lymphomas, and it has been infrequently reported with CD30+ lymphoproliferative diseases. [6][7][8][9][10][11][12][13][14] In the latter setting, some authors have suggested that PEH may be predictive of spontaneous resolution of the lymphoma lesions. 13 We propose that cases of ALCL with PEH actually represent a distinct subset along the spectrum of the CD30+ lymphoproliferative diseases where patients present with either a single nodule or a few nodules that spontaneously regress within a few months.…”
Section: Introductionmentioning
confidence: 99%
“…[66][67][68] Pseudoepitheliomatous hyperplasia can lead to confusion with squamous cell carcinoma. 69 The patterns of skin infiltration in LyP are highly variable and correlate with the age of the lesions and the degree of chronicity in a given patient. Three histologic variants-types A, B, and C-have been described based on cytologic features and the number of large cells.…”
Section: Distinguishing Pathologic Features Of Systemic Alcl C-alclmentioning
confidence: 99%